Expanding the clinical and mutational spectrum of Kaufman oculocerebrofacial syndrome with biallelic UBE3B mutations - Basel-Vanagaite, Lina; Yilmaz, Rustem; Tang, Sha; Reuter, Miriam; Rahner, Nils; Grange, Dorothy K.; Mortenson, Megan; Koty, Patrick; Feenstra, Heather; Gonzalez, Kelly D. Farwell; Sticht, Heinrich; Boddaert, Nathalie; et al. (Human genetics, 2014)
Biallelic mutations of UBE3B have recently been shown to cause Kaufman oculocerebrofacial syndrome (also reported as blepharophimosis-ptosis-intellectual disability syndrome), an autosomal recessive condition characterized by hypotonia, developmental delay, intellectual disability, congenital anomalies, characteristic facial dysmorphic features, and low cholesterol levels. To date, six patients with either missense mutations affecting the UBE3B HECT domain or truncating mutations have been described. Here, we report on the identification of homozygous or compound heterozygous UBE3B mutations in six additional patients from five unrelated families using either targeted UBE3B sequencing in individuals with suggestive facial dysmorphic features, or exome sequencing. Our results expand the clinical and mutational spectrum of the UBE3B-related disorder in several ways. First, we have identified UBE3B mutations in individuals who previously received distinct clinical diagnoses: two sibs with Toriello-Carey syndrome as well as the patient reported to have a "new" syndrome by Buntinx and Majewski in 1990. Second, we describe the adult phenotype and clinical variability of the syndrome. Third, we report on the first instance of homozygous missense alterations outside the HECT domain of UBE3B, observed in a patient with mildly dysmorphic facial features. We conclude that UBE3B mutations cause a clinically recognizable and possibly underdiagnosed syndrome characterized by distinct craniofacial features, hypotonia, failure to thrive, eye abnormalities, other congenital malformations, low cholesterol levels, and severe intellectual disability. We review the UBE3B-associated phenotypes, including forms that can mimick Toriello-Carey syndrome, and suggest the single designation "Kaufman oculocerebrofacial syndrome".
EVALuna2:9227